(3GdZjK GdefSLe aj TQM dGejI GdYLe ddWaQGFis - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s; (3GdWZQGFj , GdMSjf Hf Ydj Hf eMeO Hf YHO GdUeO GdCUHgGfj GdWZQGfj, eDjO GdOjf CHh ESeGYjd,J (B513 (3g` s
(3ChdgG (B:s
(3jHOC HTQM HjJ GdWZQGFi (B: (3jTai dOjZ GdYhGdi ai HjhJge Hfgdg ef ZOjQ GdNeQh GdYSd Hbhdg (B: (3GddZI (B: (3dOZI GdYbQH jdOZg dOZkG agh edOhZ s
(3BNQgG (B:s
(3jfJgi CKfGA TQM Hjf GdWZQGFi (B: (3bO QTMhc dCeQ Ef aWfJ dg aCQHG HfaSc Cf JQYG eY Gdged Hbhdg (B: (3hWGHb GdThb dgai HgG OehYi aVdG Hjf LGO hHGO s
(3HgG fXGe GdJYbjHIs
(3LRA efgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B340s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdCOHs